(untitled) (Konferensiyalar | Conferences, 2024)
Technology has become a crucial part of learning throughout the world. Teachers are nurturing learners of the 21st century who grow up with technology, computers, gadgets, and internet connection. Technology has been an expanse of their lives, especially their academic objectives. Technology is more valuable for EFL learners as it gives opportunities for learners to connect a wide range of information. Technology is interconnected with learner autonomy, where students can learn independently in their normal pace. It also helps learners collaborate with foreign learners and enhance language learning through several digital media by applying the Internet to access a wide range of reliable sources, materials, and tasks. To consider the relationship between student learning and the efficient combination of technology, this study provides an overview of the demands and tools for learning English in modern society. It will explore contemporary reforms in higher school to adjust to a new generation of the digital era.